To Individualize the Management Care of High-Risk Infants With Oral Feeding Challenges: What Do We Know? What Can We Do? - Lau, Chantal (Frontiers in Pediatrics, 2020)
The increase in preterm infants’ survival over the last 30 years has shed light over their inability to feed by mouth safely and efficiently. With adverse events such as increased risks for oxygen desaturation, bradycardia, penetration/aspiration, infants’ hospitalization in neonatal intensive care units (NICUs) are understandably prolonged. Unfortunately, this leads to delayed mother-infant reunion, maternal stress, breastfeeding obstacles, and increased medical costs. Such impediments have stimulated clinicians and researchers to better understand the underlying causes and develop evidence-based solutions to assist these infants. However, it is notable that the research-to-practice translation of this knowledge has been limited as there are still no validated guidelines or protocols as how to best diagnose and care for these infants. This report revisits the immature physiologic functions at the root of these infants’ oral feeding difficulties, the current practices, and the recent availability of evidence-based efficacious tools and interventions. Taking advantage of the latter, it presents a renewed perspective of how management strategies can be tailored to the specific needs of individual patients.